Foreign university involvement in sustainable new town planning in provincial China - David J. Edelman; Menelaos Triantafillou (Journal of Urban Management, 2012)
Recent concern with sustainable urban development has focused on the widespread development of new towns and the expansion of cities throughout China. In recent decades, an increasing number of planning and design professionals in the United States and Europe have undertaken consulting work in China. This study examines the first instance of a Chinese city funding an American academic planning unit to create a conceptual plan for a new town. The School of Planning from the University of Cincinnati was commissioned to prepare the conceptual plan for the Anyang Eastern New Town. Prior to the drafting of the plan, faculty and students visited the site on a reconnaissance and data gathering mission, undertook research and studio work, organized presentations, and navigated the labyrinthine bureaucracy at the local, provincial, and national levels. These experiences differ considerably from those encountered in places such as Shanghai and the southern coastal plain region. This article identifies a number of issues that play a key role in the success of projects involving American or European Universities in conjunction with the Chinese government, particularly provincial authorities. This paper provides a valuable reference for any organization involved in such undertakings.
Keywords: 710; Chinese urban planning; provincial planning; sustainable urban design